Maternal Reticulocyte Hemoglobin as a Predictor of Neonatal Iron Deficiency and Anemia - Pekar, Cassandra E.; Haischer-Rollo, Gayle D.; Hansen, Alexandra P.; Aden, James K.; Mu, Thornton S. (American Journal of Perinatology, 2025)
Anemia in pregnancy affects 30 to 40% of women globally, with iron deficiency (ID) accounting for half of the cases. In the United States, iron-deficiency anemia (IDA) prevalence during pregnancy is approximately 5%. ID and IDA negatively affect the maternal-fetal dyad. Reticulocyte hemoglobin equivalent (RET-He) estimates functional iron stores without additional blood sampling. Monitoring RET-He in pregnant women and neonates may facilitate earlier interventions with iron supplementation. The aim is to evaluate RET-He's utility in identifying pregnant women and neonates at risk for ID and IDA.This prospective, observational study followed pregnant women with anemia. RET-He and hemoglobin (HgB) values were measured during the first and third trimesters and at delivery (umbilical cord blood). Exclusions included preterm birth, monochorionic twin gestations, and conditions complicating cord blood collection.One hundred and seventy-seven dyads were included in the study. Maternal mean HgB was 12.2 ± 1.1 and 10.8 ± 1.2 g/dL, with RET-He values of 32.7 ± 3.2 and 30.5 ± 3.6 pg in the first and third trimesters, respectively. Neonatal mean cord HgB was 15.0 ± 1.6 g/dL with RET-He of 32.9 ± 2.6 pg. Thirteen percent (n = 23) of newborns were anemic (cord HgB < 13.5 g/dL), and 7% (n = 13) of the newborns were iron-deficient (RET-He < 29 pg). Only two of these iron-deficient infants were also anemic. Maternal HgB and RET-He values were not associated with neonatal anemia. Sensitivity and specificity of maternal RET-He for predicting neonatal anemia were not helpful, but improved when predicting neonatal ID, especially in the third trimester. RET-He indicating ID in pregnant women was associated with anemia during their pregnancy.Maternal RET-He does not predict neonatal anemia but may aid in earlier maternal ID diagnoses. Most infants are born with normal HgB and RET-He values. RET-He may be useful for monitoring women with IDA during their pregnancies.
Keywords: reticulocyte hemoglobin; iron deficiency anemia; pregnancy; newborns